Effect of different insecticides against citrus psylla, Diaphorina citri (Liviidae: Hemiptera) at Ari-Tarnab, Peshawar (Zoo Botanica, 2023)
The Asian citrus psylla is one of the most serious pests of citrus, severely infest the leaves and young shoot. To evaluate the effectiveness of chemicals addressed against citrus psylla nymph and adult, the chemicals via Malathion, Lambda Cyhalothrin, Pyriproxifen and Polytrin-c were tested.  Experiment was carried out in randomized complete block design with 5 treatment including control replicated three times. Results showed that after first spray, the lowest mean population was recorded in Polytrin-c (5.97) which was statistically non-significant with Lambda cyhalothrin (6.65) and maximum population was observed in control (18.41). After second spray lowest mean population was recorded in Lambda cyhalothrin (5.773) statistically non-significant with followed by Polytrin-c (6.86) and highest mean population was recorded in control (18.16). All the applied chemicals were dominant in suppressing the pest population. Application of Lambda cyhalothrin and Polytrin-c twice at 15 days’ interval was noted fruitful in minimizing pest.
Keywords: Citrus plant; citrus psylla; polytrin-c; Peshawar